2010
DOI: 10.1007/s12328-010-0154-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel perspectives in probiotic treatment: the efficacy and unveiled mechanisms of the physiological functions

Abstract: Probiotics are defined as "live microorganisms which confer a health benefit on the host" when administered in adequate amounts, and have potential effects for maintaining intestinal development, nutrition, and treating intestinal inflammations, functional disorders, and other extra-intestinal diseases. Although the benefits of probiotics for human health were first noted over 100 years ago, the analysis of probiotic functions began in earnest only 20 years ago. Probiotics, such as some strains of Lactobacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 145 publications
(147 reference statements)
0
6
0
Order By: Relevance
“…Based on the results of etiological and pre-clinical studies of the effects of probiotics, many clinical trials have been conducted, and have suggested that probiotics are potentially useful in the treatment in IBD patients. However, the data from these studies were based on various subjects using different genera, species, strains and doses of probiotics [41,42]. The sample sizes of these studies have been relatively small, so there has been no definitive evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of etiological and pre-clinical studies of the effects of probiotics, many clinical trials have been conducted, and have suggested that probiotics are potentially useful in the treatment in IBD patients. However, the data from these studies were based on various subjects using different genera, species, strains and doses of probiotics [41,42]. The sample sizes of these studies have been relatively small, so there has been no definitive evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are viable microorganisms that, once ingested in sufficient amounts, exert health-promoting effects in humans and animals by assisting in the establishment of an intestinal population which is beneficial to the host entity and antagonistic to harmful bacteria [1][2][3][4].…”
Section: Main Characteristics Of Probioticsmentioning
confidence: 99%
“…Thus, since the extensive use of antimicrobials (e.g., antibiotics and silver sulphadiazine) could produce adverse reactions and side effects [7,8], the interest has been focussed on the use of probiotics for preventing or treating different human diseases [1,4] and for improving the performance parameters of farm animals. These probiotics can play an important role in immunological, digestive, and respiratory functions in humans [9] and can improve the body weight gain and feed conversion in farm animals [2,3].…”
Section: Main Characteristics Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics are supplements based on living microorganisms that aim health benefits for human and animals when consumed in adequate amounts [1,2]. Scientific researches show that these nutritional supplements demonstrate multiple properties, which are helpful to natural intestinal microbiota equilibrium [1], present anti-inflammatory and anti-allergenic properties [3] and improvement of immunity [4]. Most probiotic microorganism sources are bacteria, especially lactic acid bacteria [2], although some yeasts such as Saccharomyces cerevisiae and Saccharomyces boulardii have been increasingly applied to this purpose [5,6].…”
Section: Introductionmentioning
confidence: 99%